A Prospective Evaluation of the Interleukin-1 Receptor Antagonist Intron 2 Gene Polymorphism and the Risk of Myocardial Infarction - Zee, Robert Y. L.; Lunze, Karsten; Lindpaintner, Klaus; Ridker, Paul M. (Thrombosis and Haemostasis, 2001)
While an interleukin-1 receptor antagonist gene polymorphism (IL1RN-VNTR) has recently been hypothesized to be a risk factor for coronary artery disease, no prospective data relating this polymorphism to subsequent risk of coronary events are available. We therefore investigated the association between IL1RN-VNTR genotype and the incidence of myocardial infarction (MI) in a large, prospective cohort of initially healthy men. The IL1RN-VNTR was evaluated among 385 MI case subjects and an equal number of age- and smoking-matched control subjects during a 12-year follow-up. Overall, the allele and g enotype distributions were similar among cases and controls, both in the total cohort and in all subgroups evaluated. All observed genotype frequencies were in Hardy-Weinberg equilibrium. Furthermore, the relative risk in a comparison of homozygous mutant to homozygous wild-type was 0.89 (95%CI = 0.5-1.6; P = 0.9). In this large, prospective study, the IL1RN-VNTR gene polymorphism is not associated with risks of future MI. These data also highlight the importance of hypothesis testing studies in genetic epidemiology, particularly for hypotheses generated from small samples or post hoc subgroup analyses.
Keywords: IL1RN; myocardial infarction; prospective study; risk factors